Analisis Efektivitas Belanja Desa Pada Desa Tanjung Putri - Septa Soraida (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This research aims to analyze the effectiveness of Tanjung Putri village government spending from 2020-2022. This type of research is quantitative using APBDes realization report data. The research results prove that the effectiveness of Tanjung Putri village government spending has decreased from 2020-2022. In 2020 it was 87.99% and for 2021 the percentage of effectiveness decreased by 85.42%, meaning there was a decrease of 2.57% from the previous year, while in 2022 the percentage of effectiveness decreased again from the previous year, namely 81.11%. Even though there has been a decline from year to year, the regional government spending category is still in the effective category.